Raman spectra of gem‐quality variscite and metavariscite. (10th February 2017) - Fritsch, Emmanuel; Karampelas, Stefanos; Mevellec, Jean‐Yves
Abstract : Raman spectra were obtained on a set of five gems presented as massive variscite, from the three major sources of this gem‐quality material. In parallel, micro‐FTIR in reflectance and chemical analysis were performed on the same samples, to further characterize them. Surprisingly, four out of five samples are found to be metavariscite, which has been documented in gem quality only once before. Results of micro‐FTIR in reflectance confirmed this result. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Raman spectra on a set of five gems presented as variscite from the three major gem sources known were acquired, along with infrared spectra and chemical analysis. Surprisingly, four out of five samples are found to be metavariscite, which has been documented in gem quality only once before. Results of micro‐FTIR in reflectance confirmed this result.